Climatic design principles of traditional Malay architecture and its application into modern built forms : the potential and restriction / Idura Mohd Ghouse - Mohd Ghouse, Idura (2011)
In the advent of Post Modernism Architecture in Malaysia, the Traditional Malay Architecture is being forgotten and regarded as out-of-date and irrelevant. Not only the forms, but the true essence of the building functions and design principles which adapts to its climate and providing thermal comfort is no more being implemented intensively in designing buildings. Thus, the main purpose of this study was to investigate what are the potential and restriction of implementing the climatic design principles element into Modern Built Form in general. The research was also intended to find out what are the elements of Climatic Design Principles of Traditional Malay Architecture therefore to further make clear of which element is the most potential and which element is the less potential in the implementation. Through the findings, researcher was enabled to make suggestions and recommendations on addressing the restrictions and highlighting on the potentials. Building case study and structured interview was used as the method for research. Building case study was conducted on two buildings which are different in typology but both are not from the Traditional Malay Architecture era to examine on how the Climatic Design Principles of Traditional Malay Architecture is being implemented. The structured interviews were carried out among experienced personnel in the built environment (mostly with architecture background) to find out the positive and negative responds towards the implementation of Climatic Design Principles of Traditional Malay Architecture and their reasons for not doing so. The interviewees’ recommendations were also obtained from the interview which structured the solutions. It was discovered that as hard as it may seems, that the implementation of Climatic Design Principles of Traditional Malay Architecture in Modern Built Form is not that difficult. The implementation also found out to provide more convenience for a long term and sustainable architecture since the environmental friendly and energy efficiency is an important agenda in the built environment.